Developing a Scaffolded Reflective Framework for Ongoing Professional Development for Individual Language Teachers - Jin, Xiao (2017)
This dissertation proposes to develop a reflective framework for in-service teachers’ ongoing reflection, which draws on teachers’ real classroom experience- it is suggested to be conducted as an individual process with opportunities for dialogic interactions with external readings and the teacher self; it encourages teachers to reflect at technical, social and personal levels by making sure that all the reflective content is covered during their reflection. Mann and Walsh (2013) once noted that current reflective practice placed too much emphasis on the reflective outcome rather than the reflective process, which may not be helpful for teachers from different contexts. This paper aims to develop a reflective framework that focuses on its reflective process rather than product. The fundamental goal of the framework is to elevate teachers’ reflection from lower order thinking at a knowledge level to a higher analytical level, which is built upon the new version of Bloom’s (Anderson et al, 2001) taxonomy of question and the construct of scaffolding, two of which together provides a strong and supportive system to initiate, elicit, monitor, and evaluate teachers’ reflection. The planned innovation is tested by a one-month trial, which provides empirical data from not only the teacher’s but also the student’s point of view. Based on the collected evidence, the effectiveness, the potential development of the framework and its limitations are discussed.